Why FX Risk Management is broken: And what boards need to know to fix it - Håkan Jankensgård; Alf Alviniussen; Lars Oxelheim (Research Institute of Industrial Economics (IFN), 2015)
In this paper we challenge the role of Foreign Exchange Risk Management (FXRM) in corporate management. We believe it is fair to characterize FXRM, on the whole, as a legacy activity rather than something that reflects a realistic cost-benefit analysis at the enterpriselevel. The Board of Directors, as the designated guardians of the interests of shareholders, has a key role in setting the firm on a path towards a cost-efficient and centralized FXRM that preserves the firm's transparency and predictability towards the investor community. A policy conclusion from our analysis is that responsibility for FX policy should shift from the traditional Finance/Treasury orientation to a group risk function (e.g. a Chief Risk Officer) supported by a risk committee dedicated to integrated risk management.
Keywords: G30; G32; 330; Foreign exchange; risk management; transparency; risk committee; integrated risk management